2017
DOI: 10.1116/1.4974920
|View full text |Cite
|
Sign up to set email alerts
|

Boron and high-k dielectrics: Possible fourth etch stop colors for multipattern optical lithography processing

Abstract: International audienceIn a parallel investigation, the etch characteristics of materials within the Si-CO -N-H system were surveyed using two common fluorinated plasma etches used to etch SiO 2 interlayer dielectrics and SiN:H etch stop layers (CHF 3 and CF 4 /O 2 , respectively) with the goal of identifying new materials or " colors " to assist in the simplification of advanced multi-pass optical lithography. In this study, we investigat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…8 For this reason, HF was included in the X−F structures. As mentioned previously, Dhungana et al 13 identified CH 3 F and CF 4 chemistries as uniquely poised for high etch rates for Al 2 O 3 and thus merits investigation here too. To complete the reaction scheme (eq 1) the calculations were also carried out to OH − , H 2 O, CH 3 OH, and CF 3 OH structures as reaction products, respectively.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 76%
See 1 more Smart Citation
“…8 For this reason, HF was included in the X−F structures. As mentioned previously, Dhungana et al 13 identified CH 3 F and CF 4 chemistries as uniquely poised for high etch rates for Al 2 O 3 and thus merits investigation here too. To complete the reaction scheme (eq 1) the calculations were also carried out to OH − , H 2 O, CH 3 OH, and CF 3 OH structures as reaction products, respectively.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 76%
“…Thus, the wet and dry (plasma) chemistry required to selectively remove alumina (i.e., etching) has led to the identification of key chemical interactions that also have importance to energetic material applications. For example, Dhungana et al 13 specifically investigated etching of Al 2 O 3 using CF 4 and CHF 3 chemistries, and their findings show high etch rates for these chemistries and the feasibility for multipattern optical lithography processing.…”
Section: ■ Introductionmentioning
confidence: 99%
“…85,86 The piezoelectric properties of AlN 87 have additionally made it of interest as a transducer material in surface acoustic wave and NEM devices. 43,88 The high resistance of AlN to fluorinated plasmas 89 has further lead to its use as a plasma etch stop, 33 hard mask, 90,91 and Cu capping layer 33 in microelectronic device applications.…”
Section: Ecs Journal Of Solid State Science and Technology 6 (10) N1mentioning
confidence: 99%
“…We focus on carboranethiol SAMs on copper, based on the archetypal thiol–metal monolayer chemistry. , Carboranethiols have been previously shown to form ∼1 nm thick monolayers on a series of metals, , with demonstration of corrosion resistance on silver and the ability to modify the surface electronic properties of gold, , silver, and germanium . The unique properties of boron-based materials, and carborane-based materials in particular, including mechanical, thermal, and chemical robustness, unique etch chemistry, as well as tunable electronic, optical, and electrical properties, , make these of interest for a multitude of additional nanoelectronic applications including barrier layers, etch stops, and other patterning assist layers. …”
Section: Introductionmentioning
confidence: 99%